2011
DOI: 10.1128/jcm.01814-10
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Patterns of Human Respiratory Picornavirus Species, Including the Newly Identified Group C Rhinoviruses, during a 1-Year Surveillance of a Hospitalized Patient Population in Italy

Abstract: Human rhinovirus species C (HRV-C) was the second most common HRV species detected in hospitalized patients in Italy with acute respiratory disease during a 1-year surveillance period. Sequencing of the picornavirus VP4/VP2 region allowed molecular typing of HRV-A and HRV-B and provisional typing of HRV-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 23 publications
4
50
1
Order By: Relevance
“…Previous reports suggested that HRV-C is associated with more severe illness than HRV-A or HRV-B (19,32,43,47). More recent studies show that HRV-A as well as HRV-C are the most prevalent HRVs identified in hospitalized children (7,27,37,41,49), while HRV-C infection is associated with an increase in hospitalization events in atopic children (4). The role of HRVs in respiratory disease is currently an area of intense research, and the emerging data indicate a significant role for HRV-C in lower respiratory tract disease, particularly in children (10,21,22,26,30,38,48).…”
mentioning
confidence: 99%
“…Previous reports suggested that HRV-C is associated with more severe illness than HRV-A or HRV-B (19,32,43,47). More recent studies show that HRV-A as well as HRV-C are the most prevalent HRVs identified in hospitalized children (7,27,37,41,49), while HRV-C infection is associated with an increase in hospitalization events in atopic children (4). The role of HRVs in respiratory disease is currently an area of intense research, and the emerging data indicate a significant role for HRV-C in lower respiratory tract disease, particularly in children (10,21,22,26,30,38,48).…”
mentioning
confidence: 99%
“…These children, however, had no neurological symptoms, unlike those in reports from Colorado and California (20,21). Additionally, EV-D68 infection in Thailand paralleled peak influenza outbreak during the rainy season, which differs from the EV-D68 pattern observed in the summer and autumn elsewhere (26,27).…”
contrasting
confidence: 46%
“…After the first isolation in 1962 from four children with respiratory illness, EV68 has been isolated rarely. 3,4,[7][8][9][10][11][12] Detailed clinical and epidemiological data are mostly limited or even lacking.…”
Section: Discussionmentioning
confidence: 99%